2013
DOI: 10.1039/c2ta00986b
|View full text |Cite
|
Sign up to set email alerts
|

Improved supercapacitor performance of MnO2–graphene composites constructed using a supercritical fluid and wrapped with an ionic liquid

Abstract: Supercritical CO 2 (SCCO 2 ) is used to synthesize MnO 2 . This process is found to be promising for producing oxide nanorods ($5 nm in diameter) with little agglomeration. With suitable SCCO 2 pressure and temperature, nanocrystalline a-MnO 2 with an extremely high surface area of 245 m 2 g À1 (versus 80 m 2 g À1 for the oxide prepared in ambient air) was obtained. Introduction of graphene nanosheets and carbon nanotubes into MnO 2 with and without the aid of SCCO 2 is compared. SCCO 2 can help debundle the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 65 publications
(61 reference statements)
0
32
0
Order By: Relevance
“…[44,45] To decorate Ni nanoparticles onto Fe/CNTs, nickel(II) acetylacetonate (10 mg;S igma-Aldrich;9 9.9 %) and Fe/CNTs( 40 mg) were loaded into a5 00 mL stainless steel autoclave. The graphene nanosheets were prepared using am odified Staudenmaier method, as reported in our previous work.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[44,45] To decorate Ni nanoparticles onto Fe/CNTs, nickel(II) acetylacetonate (10 mg;S igma-Aldrich;9 9.9 %) and Fe/CNTs( 40 mg) were loaded into a5 00 mL stainless steel autoclave. The graphene nanosheets were prepared using am odified Staudenmaier method, as reported in our previous work.…”
Section: Methodsmentioning
confidence: 99%
“…The graphene nanosheets were prepared using am odified Staudenmaier method, as reported in our previous work. [44,45] To decorate Ni nanoparticles onto Fe/CNTs, nickel(II) acetylacetonate (10 mg;S igma-Aldrich;9 9.9 %) and Fe/CNTs( 40 mg) were loaded into a5 00 mL stainless steel autoclave. Methanol (50 mL; TEDIA;99.9 %) was added as solvent miscible with SCCO 2 .Dimethyl amine borane (2 mg;T CI;9 5%)w as used as reducing agent.…”
Section: Methodsmentioning
confidence: 99%
“…[26][27][28][29][30][31] We attribute the outstanding capacitive behaviour of graphene hollow spheres to their unique spherical structure (the graphene hollow spheres can maintain their structure aer being processed to fabricate supercapacitor electrodes (ESI, Fig. S3 †)).…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…The readily accessible supercritical conditions, together with its abundance, low cost, non-flammability, and non-toxicity, have made supercritical carbon dioxide (scCO 2 ) promising for manufacturing various nanosize materials [21][22][23][24][25]. A few investigations showed that the nanoparticles possessed smaller size, narrower size distribution and more homogeneous distribution in the composites synthesized with assistance of scCO 2 , compared with the ones prepared without the assistance of scCO 2 [26][27][28][29]. The composites decorated with nanoparticles with the assistance of scCO 2 exhibit much better properties in applications.…”
Section: Introductionmentioning
confidence: 98%